Effects of feedback on the decrease in academic plagiarism in high school students (Revista Innova Educación, 2019)
The objective of the study was to develop and evaluate the results of a strategy to reduce academic plagiarism in an educational institution. The sample consisted of 39 students (56.4%, women) of first year of high school of the 2018-2019 academic year who responded to an online form designed to collect information on the frequency of academic plagiarism and the actions to prevent it, as well as the factors most important that can cause it. The educational intervention was designed in six sessions of 50 min. The frequency of plagiarism was high among the participants, which correlated negatively with the actions taken to prevent it independent of sex and academic performance. Ignorance of what is academic plagiarism, how to prevent it and procrastination were the most relevant causes. 71.4% of the students reduced their frequency of academic plagiarism, while 64.3% increase the frequency of actions to prevent it. This methodology is simple and quick in decision making to identify and reduce problems in the educational field.
Keywords: Academic plagiarism; academic dishonesty; academic fraud